Pengaruh Penerapan Metode Akumulasi Harga Pokok Produksi Dalam Menentukan Harga Jual Studi Kasus pada Divisi Garment PT Mitrasejati Muliaindustri - Edison, Edison; Hasibuan, David H.M.; Hendri, Hendri (Jurnal Ilmiah Ranggagading (JIR), 2011)
In current condition where economy is being instable and competition is increasing, generally companies have dofficulties in running their business. This problems are experienced by the companies engaged to manufacturing as well, either the companies which produce massively or which produce depending on an order. Every manufacturing company is required to improve efficiency and effectiveness in all fields to achieve the companiesâ main goal, that is earning profits. One point needs to be considered, that is the use of an appropriate method to determine production cost. For this case, of course, itâs not free from production cost spent to produce the products. This production cost is a very important cost element in determining production cost. Therefore, it needs an appropriate method to calculate the amount of production cost. The method used to calculate the cost of goods manufactured by PT Mitrasejati Muliaindustri is job order costing method. In this method the production cost of each product is clearly separated from raw materials cost, direct labour cost, and factory overhead cost. The author conducted this research by case study and utilized descriptive method, by collecting data of job order production cost contained in the company. After the production cost data had been collected, the production cost was calculated using job order costing method. The percentage of profit expected is based on standard established, but the order thatâs ordered with a design desired by consumers is based on managementâs policy. Likewise, the standard calculation of overhead cost amounted to 75% set by management. Based on the author got through the research, it can be concluded that applying the accumulation method of production cost (the company used job order costing method) have significant influence in determining the price. Thus, the calculation of production cost must be done carefully and accurately by considering the amount of charge used in the production process.